Entre sistemas e poderes: uma compreensão histórica da autonomia do judiciário e da independência dos juízes no Brasil - Garcia, Fábio Henrique Falcone (2013)
This study has sought to provide subsidies for understanding the current situation of Brazilian Judiciary from a historical perspective that takes into account the relationship of that Power with other bodies of State power and society (autonomy), and judges relationship to other domains of the own judiciary that serves as condition of its activity (independence). Thus, the study focused not only on retaking the normative evolution of the Constitutions, but also on relationships between justice and society, between the powers and among different judiciaries that the political organizational structure can recognize. The study has sought to identify the bases of the Brazilian judiciary from Portuguese legal political structure, in a pluralistic way, identifying the circumstances of the transposition of this model to the Colony. The role of the Bahia s Court Relação in the organization of the political-administrative period was emphasized. Subsequently, the study touched on the issue of building the Brazilian State, on the Empire, and relationships between the State and the peculiar way of understanding the legal system, which reflected in the way the Republic was installed and how it formed the legal culture of the twentieth century. Legal culture that, in turn, involved a positivist view of science of its own time, but that was related to a still linked power, social, political and economic structures of a pre-capitalist State. The concern was to analyze how the liberal legal culture was formed and how it was related to that structure. The Constitutions of the twentieth century were addressed, too, from that perspective. The study was based on two axes: on the one hand, to identification of the relationship between the autonomy of the judiciary and its relationships with other powers; on the other hand, the verification of judges situation and their relationship with the institution regarding their independence. The aim was to reconstruct a history of the judiciary autonomy in Brazil, recognizing its situation as an arm of the political system, to enable the analysis of how independent the judge s condition is, identifying the way the instruments of control and pressure were part of the performance of these judges throughout history. Therewith, the study aims to assess whether the judiciary independence is or not a postulate or merely rhetorical for structuring the State. In the final part of the study an analysis of the transformation of the judiciary in recent decades was done, focusing on the crisis, movements and doctrines which affected its reform, seeking to reveal the risks of a legal project supposedly liberal but concretely homogenizer and possibly totalitarian